PENGARUH KUALITAS PRODUK DAN PENGGUNAAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA KECIL MENENGAH RUMAH KUE DELINA TANGERANG SELATAN - Sulaiman Sulaiman; Suparjono Suparjono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Online business in the era of digital communication is in great demand by people. By utilizing social media online, it makes it easy for everyone to explore anywhere without being limited by time and distance. Rumah Kue Delina is a brand of home industry products or small and medium businesses engaged in the culinary business domiciled in the South Tangerang area that has utilized online sales. This study aims to determine whether there is a positive and significant effect between product quality and the use of social media either partially or simultaneously on purchasing decisions in Small and Medium Enterprises Delina Cake House, South Tangerang. This study uses quantitative methods, the population of Delina Cake House customers is approximately 600 people, by using incidental sampling obtained 75 respondents. Data collection methods used were observation and questionnaires, data analysis methods used were descriptive analysis and statistical analysis of multiple linear regression techniques, correlation analysis, simultaneous F test, partial t test, and coefficient of determination test. From the correlation analysis, it can be concluded that there is a strong correlation between product quality and purchasing decisions, and a very strong correlation between the use of social media and purchasing decisions. From the results of the regression analysis obtained multiple linear regression equation Y = 0.500 + 0.079 X1 + 1.008 X2. Partial t-test shows that product quality partially has a significant effect on purchasing decisions by 57.3% while 42, 7% is influenced by other variables and the use of social media partially has a significant effect on purchasing decisions by 76.8% while 23.2% is influenced by other variables. Simultaneous F-test shows that product quality and use of social media simultaneously affect purchasing decisions at the Small and Medium Business of Delina Cake House, South Tangerang by 76.9% while 23.1% is influenced by other variables not discussed in this study.